AB1041 Prevalence of Latent Tuberculosis Infection in Rheumatoid Arthritis Patients: Findings from A United Nations National Study. (10th June 2014) - Mehta, B.; Shi, Q.; Sule, S.; Efthimiou, P.
Abstract : Background: The risk of latent tuberculosis infection (LTBI) is increased in patients with rheumatoid arthritis (RA) than in the general population. Additionally, RA patients may develop pulmonary complications and are more susceptible to respiratory infections. While tuberculosis (TB) was previously considered a problem only in developing countries, it is now a growing concern also in the industrialized world. Therefore, it is important to study the prevalence of LTBI in the RA population, especially with the current dominant role of the new biological therapies in RA therapeutics. Objectives: To identify the prevalence of LTBI among RA patients and associated risk factors. Methods: We interrogated the NIS database, the largest all-payer inpatient care database in the United States, with approximately 8 million hospitalizations each year. Our search included all adult RA patients with a discharge diagnosis of RA (ICD-9 code 714.0). LTBI prevalence was identified by ICD-9 code 795.5. We did a frequency analysis of epidemiological variables of RA patients with and without LTBI. Discharge weights were used to enable nationwide estimates. Results: The total number of RA patients identified were 530, 018. Amongst them, LTBI was prevalent in 511 patients (0.1%) whereas LTBI in the hospitalized population was diagnosed in 24, 332 of 32, 896, 347 patients in the dataset (0.07%). We compared the data of patients with RA and LTBI with that of RA patients not having LTBI (Table 1 ). Females, African Americans and smokers had a 5% higher prevalence of LTBI. Additionally, LTBI was 2.5 times more prevalent in RA patients with lung cancer and 3.75 times more prevalent in Hispanic RA patients. Conclusions: LTBI was 33% more prevalent in RA patients compared to other hospitalized patients in a nationwide inpatient registry. Risk factors associated with increased LTBI prevalence were history of smoking, lung cancer, Hispanic ethnicity, and African American race. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4835